The first occurrence of Silurian sponge spicules of the Precordillera, San Juan Province, Argentina - Beresi, Matilde S. (2010)
An association of silicified spicules of hexactinellid sponges was collected from Silurian sandstones at the top of the La Chilca Formation, outcropping at Cerro del Fuerte, near Jáchal, San Juan Province. These spicules are the first to be recorded from the Silurian of the Precordillera. The spicules were extracted by means of acetic acid treatment from yellowish coarse sandstones with carbonate cement and associated fragmented braquiopod shells. The age of the upper La Chilca Formation ranges from late Llandovery to early Wenlock, based on graptolites and brachiopods. The spicule association is only composed by hexactins (triaxons), the basic type of megasclere of the class Hexactinellida (Phylum Porifera). These sponges secrete siliceous elements that confer strength and protect them from physical perturbations. The spicules can subsequently fuse in rigid dictyonal frameworks. In the hexactins here studied, some rays are somewhat broken, but they clearly show the six rays with 90º angles between their rays. These spicules are the only microfauna found in the sandstones. No conodonts have been recovered in these levels. These spicules are common within the Class Hexactinellida, and they cannot be attributed to any specific hexactinellid taxon. These sponges are mostly confined to quiet, deep and silicon-rich environments which have no lithological record in this Silurian section. Consequently, these spicules restricted to outer platform and peri-platform were transported towards the shallow sandstone environments. Its occurrence reveals the existence of a hexactinellid fauna, which flourished in deep waters with low energy and mud substratum during the Early Silurian of the Precordillera. The greater abundance of sponge skeletons in the fossil record corresponds to periods of high sea level of the Phanerozoic oceans, whereas almost no sponge spicules have been found during the periods of low sea level as for example could have occurred during the Llandovery of the Precordillera.